Frequency of antibodies against Influenza A virus in well-managed pig farms with a history of respiratory clinical signs in the regions of Lima, Ica and Arequipa - Flores Lava, Lucero (2023)
In Peru there is clinical evidence of the Influenza A virus (VIA) and the presence of antibodies against the VIA in pigs, but there are no official reports of frequency in pig farms in the country. The aim of the study was to determine the frequency of antibodies against VIA in technical farms in Lima, Ica and Arequipa with a history of respiratory problems. Blood samples were obtained from eight age groups of pigs during 2020-2021. Antibodies against VIA were detected using a blocking ELISA test (IDEXX, USA). A total of 283 serum samples from Lima, 287 from Ica and 288 from Arequipa were processed. The overall frequency of antibodies against VIA was 24.9% (95% CI 22.0 – 27.8); while in Lima, Ica and Arequipa it was 33.2% (95% CI 27.8 - 39.0), 19.5% (95% CI 15.1 - 24.6) and 22.2% (95% CI 17.6 - 27.5), respectively. The logistic regression analysis showed that in the Lima region, the age group 0 (up to 21 days) and 5 (91 to 110 days) had a greater chance of presenting antibodies against VIA, although age was not considered a risk factor (OR<1).